Utilization of a precision medicine genetic and psychosocial approach in outcome assessment of bariatric weight loss surgery: a narrative review - Hanna, Colin; Comstock, Fiona; Chatrath, Shtakshe; Posner, Alan; Butsch, John; Blum, Kenneth; Gold, Mark S.; Georger, Lesley; Mastrandrea, Lucy D.; Quattrin, Teresa; Thanos, Panayotis K. (Frontiers in Public Health, 2025)
The obesity epidemic has become a global public health issue, impacting more than one billion people worldwide. 9% of the US population, or 28.8 million Americans will have an eating disorder in their lifetime. In fact, global eating disorder prevalence increased from 3.5% to 7.8% between 2000 and 2018. In spite of the fact that less than 6% of people with an eating disorder are medically underweight, it is indeed an important factor when considering issues related to obesity. This public health problem is often described as being caused by various genetic and psychosocial factors. One of the most effective strategies for treating morbid obesity and achieving significant weight loss is bariatric surgery. Recent focus on precision medicine approaches has expanded into bariatric surgery in an effort to better understand and achieve improved outcomes and reduce risk for post-operative weight regain and addiction transfers during the recovery process. Addiction transfers, including substance and non-substance addictions, are well established concerns for post-bariatric patients. This review details the genetic, molecular and psychosocial factors that can be utilized to inform and guide personalized treatment. Additionally, this review details some of the molecular mechanisms including dysregulation of catecholamine signaling as well as other neurotransmitter systems relevant to help further understand recovery science.